Translations of poetry from Danish and Norwegian (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
The selected poems here introduce the Bulgarian reading audience to both well-known and lesser-known representatives of contemporary Norwegian and Danish poetic art.